Lateral soft-tissue release through a medial incision: Anatomic comparison of two techniques. Issue 2 (June 2015) - Simons, Paul; Klos, Kajetan; Loracher, Clemens; Skulev, Hristo K.; Gras, Florian; Hofmann, Gunther O.; Fröber, Rosemarie
Highlights Techniques for a lateral release via a medial incision were examined. Release was performed using a transarticular approach or a dorsal flap. In this comparison the transarticular release provides benefits.